2020
DOI: 10.1111/jocs.14469
|View full text |Cite
|
Sign up to set email alerts
|

Association of tethering of the second‐order chords and prolapse of the first‐order chords of the anterior leaflet: A risk factor for early and late repair failure

Abstract: Background and Aim Second‐order chord tethering of the anterior leaflet is a risk factor for failure of posterior leaflet prolapse repair. Materials and Methods We describe two cases of second‐order chord tethering of the anterior leaflet associated with severe mitral regurgitation due to prolapse or chordal rupture of the anterior leaflet, causing early and late failure of repair. Results We described two cases where this phenomenon happened. Conclusions Our cases demonstrate that the second‐order chords of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
2

Relationship

5
2

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 7 publications
0
13
0
Order By: Relevance
“…We have termed this surgical approach “surgical mitral plasticity.” 48 To complete what nature could not, the AL has to be augmented and lengthened (by an autologous glutaraldehyde‐treated or heterologous pericardial patch or any biological patch) and the second‐order chords have to be cut to increase the effective AL length and area (Figure 11). It is worth emphasizing the necessity of second‐order chords transection, as the fibrotic process, once started, can be progressive 49 . Moreover, by eliminating apical tethering, the AL can recover its normal curvature by removal, or reduction, of the tenting area.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We have termed this surgical approach “surgical mitral plasticity.” 48 To complete what nature could not, the AL has to be augmented and lengthened (by an autologous glutaraldehyde‐treated or heterologous pericardial patch or any biological patch) and the second‐order chords have to be cut to increase the effective AL length and area (Figure 11). It is worth emphasizing the necessity of second‐order chords transection, as the fibrotic process, once started, can be progressive 49 . Moreover, by eliminating apical tethering, the AL can recover its normal curvature by removal, or reduction, of the tenting area.…”
Section: Resultsmentioning
confidence: 99%
“…It is worth emphasizing the necessity of second-order chords transection, as the fibrotic process, once started, can be progressive. 49 Moreover, by eliminating apical tethering, the AL can recover its normal curvature by removal, or reduction, of the tenting area. In selected cases, when the AL is sufficiently long, it is not necessary to augment it, but chordal cutting, performed through aortotomy, is sufficient ( Figure 12).…”
mentioning
confidence: 99%
“…AML tethering in patients with PML prolapse was demonstrated to be associated with unfavorable postprocedural residual MR after surgical repair ( 21 ). Moreover, regional leaflet tethering can coexist with prolapse in AML and/or PML and, more importantly, could also affect surgical repair as a risk factor for MR occurrence ( 10 , 11 , 22 ). Hence, tenting volume may be an integrated factor to evaluate the tethering severity of the entire MV leaflet to predict residual MR 2+ immediately after interventional EE repair.…”
Section: Discussionmentioning
confidence: 99%
“…Experimentally, it was demonstrated that MR, created by making a hole in the PL, was able to induce AL remodelling 33 . Moreover, tethering of the second-order chordae have been demonstrated in patients with prolapse of the PL 34,35 and prolapse or chordal rupture of the AL 36 .…”
Section: When To Cut the Second-order Chordaementioning
confidence: 97%